1999
DOI: 10.1080/02724939992310
|View full text |Cite
|
Sign up to set email alerts
|

Pre-school follow-up of a cohort of children with myelomeningocele in Cape Town, South Africa

Abstract: A cohort of South African children with myelomeningocele was followed for 5 years. Fifty-three were from metropolitan Cape Town and 65 from rural areas including the tribal region of Transkei. The mean general developmental quotient (GQ) at 5 years of age was lower than that previously reported. Black and coloured children had lower GQs than white children, but there were no significant differences between those from the urban and the rural areas. Early closure of the lesion and delivery by caesarean section w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
1
3
1
Order By: Relevance
“…The lumbar spine was most affected, confirmed by other studies (11,12), though when considered in isolation, no predominance between upper and lower lumbar segments was found. In our study, no child presented lesion at cervical spine.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The lumbar spine was most affected, confirmed by other studies (11,12), though when considered in isolation, no predominance between upper and lower lumbar segments was found. In our study, no child presented lesion at cervical spine.…”
Section: Discussionsupporting
confidence: 83%
“…Hydrocephalus frequency (51,2%) was lower than rates reported in previous studies (9)(10)(11), and showed no significance in relation to walking prognosis in myelomeningocele children. However, functional independence in adolescents presenting myelomeningocele, evaluated by means of the Functional Independence Measure (FIM), suffered modifications according to the presence or absence of hydrocephalus, locomotion dominion, personal hygiene and transferences (9).…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Recent population‐based data from Atlanta, Georgia (USA) indicate that survival among individuals with spina bifida is approximately 87% at 1 year, and 78% at 17 years [Wong and Paulozzi, 2001]. However, affected individuals are at risk for a range of physical and developmental disabilities [Althouse and Wald, 1980; Casari and Farrall, 1998; Buccimazza et al, 1999; Singhal and Mathew, 1999; Bowman et al, 2001], and experience excess mortality into the adult years [Hunt, 1999; Singhal and Mathew, 1999; McDonnell and McCann, 2000; Bowman et al, 2001].…”
Section: Introductionmentioning
confidence: 99%